Effects of Tadalafil Once-Daily or On-Demand vs Placebo on Return to Baseline Erectile Function After Bilateral Nerve-Sparing Radical Prostatectomy – Results from a Randomized Controlled Trial (REACTT). Issue 4 (1st April 2016) - Mulhall, John P.; Brock, Gerald; Oelke, Matthias; Fode, Mikkel; Probst, Kai A.; Henneges, Carsten; d'Anzeo, Gianluca; Rossi, Andrea; Büttner, Hartwig
ABSTRACT: Introduction and Aim: The multicenter, randomized, double-blind, double-dummy, placebo-controlled REACTT trial suggested that treatment with tadalafil once daily (OaD) started early after bilateral nerve-sparing radical prostatectomy (nsRP) for prostate cancer may contribute to erectile function (EF)-recovery, which was predefined as achieving an International Index of Erectile Function (IIEF)-EF score ≥22. Here, we report descriptive post-hoc analyses, using the more strict definition for EF-recovery of returning back to the pre-surgery IIEF-EF-level ("back-to-baseline analysis"). Methods: REACTT included 422 men <68 years with adenocarcinoma of the prostate and preoperative IIEF-EF ≥22 who underwent nsRP at 50 centers from 9 European countries and Canada. Patients were randomized post-nsRP 1:1:1 to 9-month double-blind treatment (DBT) with tadalafil 5 mg OaD (n = 139), tadalafil 20 mg on-demand ( pro-re-nata, PRN; n = 142), or placebo (n = 141), followed by 6-week drug-free washout (DFW) and 3-month open-label tadalafil OaD treatment (OLT). Main Outcome Measures: Proportion of patients returning to their preoperative IIEF-EF category (22–25 or ≥26) at the end of DBT, DFW, and OLT. Results: Overall, 92.4% of patients had pre-surgery (baseline) IIEF-EF scores ≥26 (tadalafil OaD 94.2%, PRN 91.6%, placebo 91.5%), 7.4% had IIEF-EF 22–25. At the end of DBT, 22.3% of patients on tadalafil OaD had achieved "back-to-baseline" IIEF-EF, compared with 11.3% on tadalafil PRN and 7.8% on placebo. Of all 58 patients "back-to-baseline" at the end of DBT, only 1 PRN-group patient had started from a baseline IIEF-EF <26. The treatment-group difference at the end of DBT was not maintained after DFW. After 3 months of OLT with tadalafil OaD, the proportion of patients with "back-to-baseline" IIEF-EF had almost doubled in all 3 groups. Conclusion: Changing the definition for EF-recovery from IIEF-EF ≥22 to the more strict definition of "returning back-to-baseline IIEF-EF" had no major impact. Tadalafil OaD started early after nsRP improved drug-assisted EF, but had no effect on unassisted EF following treatment cessation after 9 months.